A educação das crianças menores de 06 anos sobre a perspectiva de Heloísa Marinho, Nazira Féres Abi-Sáber, Celina Airlie Nina e Odilon de Andrade Filho : uma análise de suas ideias pedagógicas (1934-1971) - Varotto-Machado, Michele (2015)
Heloísa Marinho, Celina Airlie Nina, Nazira Féres Abi-Sáber and Odilon de Andrade Filho have a range of bibliographic production, and research articles regarding the understanding of the child under 06 years in Brazil. Anchored directly to government agencies of their period, the authors sought to present their works in pedagogical ideas for the Early Childhood Education. Faced with this observation, we aimed to understand: The conceptions that concern the School movement would have been appropriate in Brazilian Early childhood education? How the ideals of John Dewey were implemented for the education of children under 06 years? So the main research hypothesis is the incorporation of educational ideas of John Dewey occurred in the core of the hygienist/assistentialist movement, which could have led to distortions and theoretical and methodological mistakes in the use of the Dewey school theory. Thus, our objective is: apprehend and analyze how the educational conceptions of John Dewey were appropriate to "think" the Brazilian Early Childhood Education from to 1934 to1971. As methodological procedures we base our analysis on the theoretical and methodological support of Depaepe (2000; 2005) and Certeau (2008) with regard to the consideration of the research object in its historical context, but also consider the assumptions highlighted by Depaepe (2000; 2005 ) on the "black box" of the classroom, "grammar of schooling" and educacionalization process. Therefore we conducted a literature review about the output for the children under 06 years, considering the period defined for this research. This survey, however, was made in the following journals: Revista Educação, Revista Sociedade e Educação and Revista Brasileira de Estudos Pedagógicos. Regarding proposals to lower education than 06 years in Brazil, it was possible to understand the political and pedagogical demands for this field. In this sense, we sought from the selected material understand the circularity of the ideas that were present in the context of life and production of the four authors selected as the object of our study. Heloisa Marinho, Celina Airlie Nina, Nazira Féres Abi-Saber and Odilon de Andrade Filho highlighted by the direct relationship with government agencies set up at the time to provide the shelter, protection and educational projects for young children in Brazil, among which out: the National Department of Children; National Institute of Pedagogical Studies (INEP); Brazilian-American Assistance Program Elementary Education (PABAEE) and the Center for Studies and Research Helena Antipoff the Pestalozzi Society of Brazil. These authors can be considered active and immersed in national and international debates in the field of Early Childhood Education, with: materials, discussions, guidelines, analysis and activity descriptions for the children. From the analysis of all this material it was found that the set of conceptions present in the New Education ideas were appropriated by these authors, but were used as species of "slogans" that represented the ideas of Dewey, Decroly, Montessori, Froebel, Pestalozzi and Claparede; these appeared as a discourse of "reform" and consequently thus "improving" for the Early Childhood Education.